Work-life experiences of employees with bipolar disorder - Ceylan, Faruk (İstanbul Bilgi Üniversitesi, 2019)
Abstract : The present study aims to investigate the work and workplace experiences of employees with bipolar disorder. In the modern world, people diagnosed with psychological disorders may hide their psychological disorders from third people, groups, or institutions because of the potential for exclusion from various social settings; and, the work settings would take the first place in the list. Therefore, one of the significant social issues of today is to fight against the stigma attached to psychological disorders. Even if these people might be functional following the episodes, most of the time, the work settings are reluctant to let them work. Therefore, the main research question of the study is related to professional life of employees with bipolar disorder. How working conditions, work settings, and professional interrelationships affect them is the main focus of the current study which is the first research in Turkey on this target group. The aim is not just to reveal their individual experiences but also study cultural perspectives over bipolar disorder in working environment. Semi-structured in-depth interviews were conducted with ten interviewees who are diagnosed with bipolar disorder. After the ethics approval of İstanbul Bilgi University, Çapa Medical School in Istanbul (Psychiatry Department) and Bipolar Life Association in Istanbul are reached out for the volunteers to participate in the research. Inclusion criteria were being a white-collar employee (currently working and non-working) and being diagnosed with bipolar 1 or 2 disorders. MAXQDA qualitative data analysis program was used with the analytic principles of Interpretative Phenomenological Analysis (IPA) to analyze data. The master themes emerged as follows: “the reflections of symptoms of mania in the workplace”, “the reflections of symptoms of depression in the workplace”, “disclosing the diagnosis”, “difficulties in work-life”, “working and meaning” and “society, family and human resources management professionals’ perspectives on bipolar disorder”.

Özet : Bu çalışmanın amacı bipolar bozukluk tanısı almış çalışanların iş ve işyeri deneyimlerini incelemektir. Modern dünyada, psikolojik bozukluk tanısı almış olan insanlar aldıkları tanılarını, dışlanma potansiyeli sebebiyle çeşitli sosyal ortamlardan üçüncü kişilerden, gruplardan veya kurumlardan gizleyebilir; ve iş ortamı listede ilk sırada yer almaktadır. Bu nedenle, günümüzün en önemli sosyal sorunlarından biri, psikolojik bozukluklara yönelik damgalanmaya karşı mücadele etmektir. “Bipolar bozukluk aynı zamanda semptomatik belirtileri ile az miktarda ilişkili görünen bir dizi sosyal ve mesleki komplikasyona sahiptir” (Goldberg & Harrow, 1999, s. 59). Açıkça, bu insanlar atakların ardından işlevsel olsalar bile, çoğu zaman iş ortamı onların çalışmasına izin vermekte isteksizdir. Çalışmanın temel araştırma soruları: Çalışma yaşamının hangi bileşenleri bipolar bozukluğu olan bir çalışanla ilişkilidir? Çalışma koşulları, çalışma ortamı ve profesyonel ilişkiler bipolar bozukluk tanısına sahip insanları nasıl etkiler? Bu çalışma, Türkiye'de bipolar bozukluğu olan çalışanların deneyimlerini içerecek ilk çalışma olacaktır. Amaç, sadece katılımcıların bireysel deneyimlerini ortaya koymak değil, aynı zamanda çalışma ortamında bipolar bozukluk üzerine yapılan kültürel bakış açısını da incelemektir. Yarı yapılandırılmış derinlemesine görüşmeler bipolar bozukluk tanısı almış ve iş tecrübesi olan on görüşmeci ile yapılmıştır. İstanbul Bilgi Üniversitesi’nin etik onayının ardından, İstanbul'daki ÇAPA Tıp Fakültesi (Psikiyatri Anabilim Dalı) ve Bipolar Yaşam Derneği aracılığıyla gönüllü katılımcılarla temasa geçildi. Örnekleme grubu beyaz yakalıdır ve bipolar 1 veya 2 tanısı almış olan kişilerden oluşmaktadır. Veriler, Yorumlayıcı Fenomenolojik Analiz'in analitik prensipleriyle MAXQDA nitel veri analiz programı ile analiz edilmiştir. Çalışmada, temel bulgular ana temaların “mani döneminin iş yaşamına yansımaları”, “depresif dönemin iş yaşamına yansımaları”, “tanının paylaşılması”, “iş yaşamında yaşanılan zorluklar”, “çalışmak ve anlam” ve “toplum, insan kaynakları profesyonelleri ve ailenin tanıya bakış açısı” olduğunu göstermiştir.
Bipolar bozukluk tanısı almış çalışanların iş yaşamı deneyimleri
Keywords: Bipolar bozukluk; Damgalanma; Yorumlayıcı fenomenolojik analiz; Çalışma ortamı; Bipolar disorder; Stigma; IPA; Work settings